The Effects of Air Pollutants, Particulate Matter 10 (PM10), Sulphur Dioxide (SO2) and Nitrogen Dioxide (NO2) on COVID-19 cases in Indonesia - Erwin Dariyanto (Sustainability Science and Resources)
This study aims to analyse the effects of air pollutants on the number of COVID-19 cases in Indonesia. Three pollutants, i.e. Particulate matter 10 (PM10), Sulphur dioxide (SO2) and Nitrogen dioxide (NO2), were analysed. The study covers a period of 1 March 2020 to 31 December 2020 involving data from the cities of Jakarta, Bandung, Yogyakarta, Semarang and Surabaya in Indonesia.